The plight of victims of wrongful acts committed by international organisations: a light at the end of the tunnel? - Likomwa, Ethel Tilly (Department of Public Law, 2021)
The activities and the level of influence of International Organisations (IOs) have grown extensively in recent years. This has resulted in IOs having a greater impact, both positively and negatively, on the lives of individuals. In as far as the negative impact is concerned, it is a well established principal of international law that the wrongful conduct of an IO attracts the responsibility of that IO. The reality however is that holding IOs responsible for their wrongful acts is an uphill task. In this regard, there has been an increase in calls for more effective ways of holding IOs accountable for their actions. This thesis adds its voice to those calls. The point of departure however, is that in this thesis, the question of IO responsibility is approached from the perspective of the victims of the wrongful conduct of IOs. The call for greater effectiveness in holding IOs to account is made through an illustration of the difficulties faced by those attempting to seek redress for wrongs committed by IOs. Additionally, the thesis examines the role of domestic courts and institutions in holding IOs to account. This examination is necessary in light of the increasing trend of domestic and regional courts piercing the immunity veil of an IO, where that IO has not provided alternative dispute settlement mechanisms.